Analisa semiotik denotasi, konotasi, dan mitos iklan Indomie versi 45th Anniversary di televisi - Andriyanto, Andriyanto (Universitas Tarumanagara, 2017)
This research aims to explain the meaning of denotation, connotation, and myth contained in the Indomie instant noodle ad version “45th Anniversary”. The object of this research is the Indomie advertisement version “45th Anniversary” where the advertisement is made to celebrate the 45th anniversary of Indomie and coinciding with the independence month of the Republic of Indonesia in 2017. The type of this research is descriptive research which has a complete picture of a phenomenon or event that is happening as its purpose. This research takes primary data in the form of the “45th Anniversary” Indomie advertisement which was taken from television media on one of the television programs, to make this research easier, the researcher downloaded the advertisement at one of the internet sites that have YouTube as its site domain. The study of this research theory comes from several books, previous studies, articles, journals, and other sources through internet media which contain Roland Barthes’s theories about denotation, connotation, and myth. This research attempts to analyze the “45th Anniversary” Indomie advertisement by segregating the ads into manageable sections to get an important and learned picture to be shared with others. This research focuses on the tradition of semiotic communication proposed by Craig and particularly by Roland Barthes’ semiotic theory.